Field-assisted growth of one-dimensional ZnO nanostructures with high defect density. (7th December 2020) - Phuah, Xin Li; Cho, Jaehun; Akriti,; Dou, Letian; Rheinheimer, Wolfgang; García, R Edwin; Zhang, Xinghang; Wang, Haiyan
Abstract: One-dimensional ZnO nanostructures have shown great potential in electronics, optoelectronics and electromechanical devices owing to their unique physical and chemical properties. Most of these nanostructures were grown by equilibrium processes where the defects density is controlled by thermodynamic equilibrium. In this work, flash sintering, a non-equilibrium field-assisted processing method, has been used to synthesize ZnO nanostructures. By applying a high electric field and limiting a low current flow, ZnO nanorods grew uniformly by a vapor–liquid–solid mechanism due to the extreme temperatures achieved near the hot spot. High density basal stacking faults in the nanorods along with ultraviolet excitonic emission and a red emission under room temperature demonstrate the potential of defect engineering in nanostructures via the field-assisted growth method.